Effects of Tranexamic Acid on Bleeding in Pediatric Surgeries: A Systematic Review and Meta-Analysis - Wei, Yiyong; Zhang, Yajun; Jin, Tao; Wang, Haiying; Li, Jia; Zhang, Donghang (Frontiers in Surgery, 2021)
Background: Major pediatric surgeries can cause severe intraoperative blood loss. This meta-analysis aims to evaluate the efficacy of tranexamic acid (TXA) in pediatric surgeries. Methods: We searched PubMed, Embase, Web of Science and Cochrane Library from the conception to March 31, 2021 to identify eligible randomized controlled trials (RCTs) that evaluated the efficacy of TXA in pediatric surgeries. Two reviewers choosed studies, evaluated quality, extracted data, and assessed the risk of bias independently. Mean difference (MD) was calculated as the summary statistic for continuous data. We used a random-effects model to measure mean effects. Data were generated from the corresponding 95% confidence interval (CI) using RevMan 5.3 software. Primary outcomes included intraoperative and postoperative blood loss, red blood cell (RBC) transfusion as well as fresh frozen plasma (FFP) transfusion. Results: Fifteen studies enrolling 1332 patients were included in this study. The pooled outcomes demonstrated that TXA was associated with a decreased intraoperative (MD = −1.57 mL/kg, 95%CI, −2.54 to −0.60, P = 0.002) and postoperative (MD = −7.85 mL/kg, 95%CI, −10.52 to −5.19, P < 0.001) blood loss, a decreased intraoperative (MD = −7.08 mL/kg, 95%CI, −8.01 to −6.16, P < 0.001) and postoperative (MD = −5.30 mL/kg, 95%CI, −6.89 to −3.70, P < 0.001) RBC transfusion, as well as a decreased intraoperative (MD = −2.74 mL/kg, 95%CI, −4.54 to −0.94, P = 0.003) and postoperative (MD = −6.09 mL/kg, 95%CI, −8.26 to −3.91, P < 0.001) FFP transfusion in pediatric surgeries. However, no significant difference was noted between two groups in duration of surgery (MD = −12.51 min, 95%CI −36.65 to 11.63, P = 0.31). Outcomes of intraoperative and postoperative blood loss and the duration of surgery in included studies were not pooled due to the high heterogeneity. Conclusion: This meta-analysis demonstrated that TXA was beneficial for bleeding in pediatric surgeries.